PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN HYPERMART LAMPUNG - Desi Derina Yusda; Pebriyanti Pebriyanti; Mohammad Renandi Ekatama (Jurnal Manajemen dan Bisnis (JMB), 2022)
ABSTRACT This study aims to determine the influence of organizational culture and employee job satisfaction at Hypermart Central Plaza Lampung. The data used in this study are primary data, data that comes directly from the source in the form of answers to questionnaires and secondary data on research collected from other parties, namely data on the number of employees, employee attendance and data on facilities and infrastructure. The analysis technique used is validity, reliability, classic assumptions, hypothesis testing, R2 and multiple linear regression. Based on the results of the analysis, it is revealed that simultaneously organizational culture and work environment have a positive and significant effect on job satisfaction at Hypermart Central Plaza Lampung. F count f table (50,118 3,23) with a significant level of 0,000 0.05. and partially organizational culture has a positive and significant effect on employee job satisfaction at Hypermart Central Plaza Lampung. the organizational culture variable is (6.118 1.68107) with a significant level of 0.000 0.05. while the work environment variable is (6.100 1.68107) with a significant level of 0.000 0.05. Thus, to increase employee job satisfaction, attention to organizational culture and work environment factors. Keywords: Organizational Culture, Work Environment, Job Satisfaction